A Comparative Study of the Evaluation Strategies in the LMD and Classic Systems - Rabehi, Salima (Sciences humaines, 2016)
إن تطبيق نظام" ل م د" في التعليم العالي في الجزائر مشروع طموح و لا سيما في مجال تعليم اللغات الحية و خصوصا الانجليزية,  فهو يكتسي  إذن  أهمية كبرى في المسيرة التعليمية ة التربوية. مع نظام "ل م د" جاءت دروس لم نعهدها في النظام الكلاسيكي و لا سيما فيما يخص مستوى السنة الأولى. كما يولي نظام "ل م د" أهمية قصوى للتقييم المستمر/التكويني على غير النظام الكلاسيكي، في حين هذا النوع من التقييم إجباري في النظام الجديد ل.م.د ، فهو اختياري في النظام الكلاسيكي. و سؤالنا هنا هو إلى أي مدى يعتبر هذا التقييم ناجعا خاصة عندما يكون الطلبة واعين بمدى تأثيره على نجاحهم في كل مادة نهاية كل سداسي. من خلال هذه الورقة نتطرق إلى عدة نقاط أهمها مستوى الطلبة, نقطة الامتحانات, آراء الأساتذة, المناهج و الوقت المخصص. و للوصول إلى ما نصبو إليه فلقد اعتمدنا على شريحة معينة من الأساتذة ذوي الخبرة في تدريس طلبة السنة الأولى  لقسم الانجليزية في كلا النظامين. هذا و نركز على التقويم الذي يقوم به الأساتذة كأداة جديدة لبلوغ الأهداف المسطرة. في الأخير, فإننا استخلصنا أنه على الطلبة الانتباه أكثر إلى أهمية التقييم المستمر للتمكن من معالجة القصور المرتبط بهذا الأخير.               The implementation of the new system « LMD » in Algerian higher education is an ambitious project .In the field of foreign language and especially in English, it is of great importance to the teaching/learning process. Indeed, the LMD system introduces new courses that are not given in the classic one at the level of first year classes in particular. In addition, it gives more importance to the continuous/ formative evaluation than the classic one does. Whereas the formative evaluation is optional in the classic system, it is compulsory in the new system. The main question here is to which extent is that evaluation efficient in case that the students are aware of its impact on their success by the end of each course. The major aim of this paper is to examine the validity and effectiveness of the “formative evaluation” in the LMD system. To answer the question stated above, the present paper takes the following elements as its basis: the students’ level, exam grades, teachers of systems opinions, the common courses syllabi, and the time allotted. To give credit to our claims, this paper relies on a restricted population of teachers who have the experience in teaching 1 st year students of the English language department in both systems LMD and Classic. The study spots the light on the teacher’s assessment of the new testing tool. At the end of this work, we come to the conclusion that students in the first place have to pay much more attention to the importance and validity of the continuous evaluation in order to remedy their deficiencies that are related to the latter.